Development and characterization of transdermal therapeutics system of tramadol hydrochloride - Shinde, Anil J; Garala, Kevin C; More, Harinath N (Asian Journal of Pharmaceutics (AJP), 2014)
The present work was designed to develop suitable transdermal matrix patches of tramadol hydrochloride, a non-steroidal anti-inflammatory drug, using hydroxy propyl methyl cellulose (HPMC), Eudragit RL-100 and Eudragit RS-100 with triethyl citrate as a plasticizer and dimethyl sulfoxide (DMSO) as a penetration enhancer. Different batches developed using Eudragit RL-100 : HPMC and Eudragit RS-100 : HPMC in ratio of 2 : 8, 4 : 6, 6 : 4, and 8 : 2. Drug - excipients interaction study was further carried out using Fourier transform infrared (FTIR) spectroscopic technique. Physical evaluation was performed such as moisture content, moisture uptake, tensile strength, flatness, and folding endurance. In vitro diffusion studies were performed using cellulose acetate membrane (pore size 0.45 μ) in a Franz’s diffusion cell.The concentration of diffused drug was measured using UV-visible spectrophotometer (Jasco V-530) at λmax 275 nm.The batch containing EudragitRL-100 : HPMC (8 : 2) showed 79.65% release within 12 h and batch containing Eudragit RL-100 : HPMC (2 : 8) showed only 58.30% release in 12 h. This is because that the Eudragit produce crystallization free patch.